Functions of English versus Other Languages in the Domain of Buddhism in Thailand - Preecha, Parinyaporn; Srinon, Udomkrit (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2018)
This study focuses on the functions of English versus other languages in a Thai Buddhist context. It demonstrates that English has an effect on religious practices and the use of English in the religious domain has been developed to serve the changing society. The framework for this study is based on a previous works on the language of Hindu rituals by Pandharipande (2012) and Herat (2015). It is stated that in the old days, English was excluded from Buddhist rituals in Thailand. Therefore, this paper attempts to highlight primarily research The Journal of Humanities Vol. 10 No.2 July – December 2018 99 data in a fact that: nowadays, English has an effect on religious practice and diffusion in a Thai context in some degree because (a) the media promotes it; and (b) it impacts the degree of functional load for the languages of rituals. The following research questions are examined: (1) What are the ways in which English and other languages work in the domain of Buddhism? (2) What are the main characteristics of languages and contents used by monks , scholars and other people regarding Buddhism? The content analysis was employed to focus on data analysis regarding language use in the domain of Buddhism which promotes some better understanding on religious practices. Further suggestions are made within the domain of World Englishes and functional use of languages.